Two new skinks of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from southern Vietnam - Sang Ngoc Nguyen; Luan Thanh Nguyen; Manh Van Le; Vu Dang Hoang Nguyen; Khanh Duy Phan; Thi-Dieu-Hien Vo; Robert W. Murphy; Jing Che (European Journal of Taxonomy)
Two new skinks of the genus Scincella Mittleman, 1950, from Khanh Hoa and Binh Thuan provinces, southern Vietnam, are described based on differences in morphology and nucleotide sequences. Scincella honbaensis sp. nov. is diagnosed by the following morphological characters: 28 smooth midbody scale rows; dorsal scales enlarged, six rows on back; 64 paravertebrals; 74 ventral scale rows; prefrontals in broad contact with one another; one anterior and two posterior enlarged temporals; three pairs of nuchals; 21 smooth lamellae beneath toe IV; dorsum with two longitudinal rows of black dots. Scincella auranticaudata sp. nov. is diagnosed by the following morphological characters: 34–36 smooth midbody scale rows; dorsal scales not enlarged, ½+8+½ rows on back; 67–74 paravertebrals; 65–69 ventral scale rows; prefrontals separated from or just in contact with one another; two anterior and two posterior enlarged temporals; one pairs of nuchals; 17–20 smooth lamellae beneath toe IV; hemipenis smooth, forked near the base with two long symmetrical lobes; dorsum with a vertebral line formed by large black spots. Scincella honbaensis and Scincella auranticaudata differ from their congeners by an uncorrected p-distance in COI sequences of at least 16.7% and 9.4%, respectively.